Legal Pluralism and the Rights to Pachamama - Antúnez Sánchez, Alcides; Díaz Ocampo, Eduardo (DIXI, 2018)
Aim: To show the constitutional recognition that nature has gained in the Ecuadorian nation, which has allowed it to be subject of rights and duties as a legal novelty in the construction and evolution of the 21 st century, as well as its regulatory development within positive law and public policies. Methods: For this, the historical-legal, analysis-synthesis and induction-deduction methods were em- ployed. Findings: From the last decades of the 20th century, legal pluralism has become relevant due to its impact on the social scene. While having various orientations and positions, Philosophy of Law and Sociology deal with the definition of new theoretical constructs required to address the essence of legal pluralism in the current context, reevaluating it and providing new aspects of analysis. Conclusions: The Ecuadorian State guarantees the conservation and development of the indigenous peoples’ traditional forms of coexistence and social organization since they constitute an expression of interculturality. This has had a positive effect on the constitutional protection of nature and its regulatory development based on constitutional texts.